Middle East and North Africa : another year of upheaval - Dorsey, James M. (2013)
Political turmoil and violence promise to shape events in the Middle East and North Africa this year. Monarchies are replacing republics in facing the tidal wave of reform demands in the region. Syria continues to be wracked by civil war while post-revolt nations like Egypt struggle to build a more open society.